Psilocybin - new remedy for patients with psychiatric disorders? Critical analysis of the current state of knowledge - Wąsik, Karolina; Tomaszuk, Sebastian; Wojtuś, Magda (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Nowadays, when mental disorders are considered by the World Health Organisation as a global burden, the potential usage of psychedelic drugs as supportive therapy is gaining more attention worldwide. The aim of this paper is to summarize the usefulness of psilocybin - representative of psychedelics - in psychiatric venues. In this review we describe its properties, efficacy and adverse events in treating depression, trauma and obsessive-compulsive disorders. Brief description of the state of knowledge: Psilocybin demonstrates a safety profile which does not differ from standard drugs used in therapies of psychiatric disorders. Positive results of its administration were noticed on different psychiatric scales and are considered as clinically meaningful. With depression being the most common mental disease and growing demand for new remedies, most of the conducted research is concentrated on this subject, but there is also some evidence of its purpose in the treatment of trauma and obsessive-compulsive disorders. Conclusions: Psilocybin merits further research as foregoing results of conducted studies are pointing to its efficacy. Psychedelic-assisted therapies may create noteworthy opportunities to current matter in the standard treatment of psychiatric disorders and there is a possibility that in the future in some cases they will be considered as the first line treatment. Nevertheless, still more data is needed to determine its placement in the treatments.